Mechanical Ventricular Assistance as Destination Therapy for End-Stage Heart Failure: Has it Become a First Line Therapy? - Bonacchi, Massimo; Harmelin, Guy; Bugetti, Marco; Sani, Guido (Frontiers in Surgery, 2015)
Patients with end-stage heart failure have poor quality of life and prognosis. Therapeutic options are scarce and are not available for all. Only few patients can be transplanted every year. Several medical and surgical strategies have shown limited ability to influence prognosis and quality of life. In the past years, technological progress has realized devices capable of providing appropriate hemodynamic stabilization and recovery of secondary organ failure. Recently, these devices have been assessed as definitive treatment for patients who do not qualify for transplantation or/and instead to transplantation (“destination therapy”). This indication is increasingly considered following the results of newest clinical study reporting long-term survival without device correlated adverse events using last generation devices, and acceptable quality of life. The current knowledge about destination therapy and some original data from the DAVID Study (an Italian multicenter prospective study designed to evaluate the patient’s survival rate and quality of life of patients implanted with these new devices as long-term support or destination therapy) are summarized herein. Key Points – End-stage heart failure (NYHA class IV or stage D) is a vastly growing problem, with a poor prognosis and limited therapeutic options. – Heart Transplantation is nowadays the “gold standard” treatment albeit its inability to serve to the current demand let alone the future one. – The REMATCH study has demonstrated that first generation implantable devices, even with their high number of complications (infectious and thromboembolic events), allowed an improvement of quality and duration of life compared to medical therapy. Further studies have shown that the evolution of VAD technology has reduced device-related complications and consequently improved survival and quality of life of patients with results, according to some authors, similar to cardiac transplantation at least at 2 years from the implantation. – Biotechnology advancements have led to the creation of a new generation of implantable mechanical assist devices: the continuous-flow rotary pumps. Recently entered into clinical use, they seem to represent a promising solution to end -stage – heart failure allowing long-term assistance and an adequate standard of living (Destination Therapy/Bridge to Life). – The DAVID Study, an Italian multicenter prospective study, reports encouraging results in terms of late outcome and quality of life in patients implanted with newest continuous-flow devices as destination therapy. More and more numerous studies are needed to confirm our initial data and for laying the foundations for this new therapeutic frontier face to cardiac transplantation.